Analisis dan Perancangan Sistem Informasi Penjualan UMKM Berbasis Website Menggunakan Standar ISO/IEC 25010 (Studi Kasus: Nexa Billiard Green Lake City, Cengkareng) - Bayu Aditiya Nuryansyah; Rafael Syafiq Al Fahrezi; Chairul Anwar (Journal of Information Systems and Business Technology, 2026)
Nexa Billiard is an MSME facing significant operational constraints due to conventional transaction recording systems, the absence of online table reservation facilities, and the lack of a customer relationship management database. These problems frequently trigger long queues, loss of potential revenue, and managerial difficulties in evaluating business performance. This research aims to design and implement a website-based sales information system to overcome these limitations. Software development was conducted using the Prototype model through an iterative engineering approach, with system architecture modeling depicted using the Unified Modeling Language (UML). The resulting information system successfully integrates crucial features, including table rental, centralized online reservations, logistics inventory control, and real-time automated revenue reporting. To ensure product quality and feasibility, the system was comprehensively evaluated using the ISO/IEC 25010 international testing standard. The test results indicate that this software has met the feasibility parameters in the aspects of functional suitability, usability, reliability, and performance efficiency. In conclusion, the implementation of this website-based information system is proven to simplify the complexity of daily transactions, eliminate physical queues, and provide accurate business intelligence analysis instruments, significantly increasing the operational efficiency and profitability of Nexa Billiard.